Development of dual-phase SiC/Si3N4 nanostructures on nanosized SiC particles. (1st February 2020) - Rajavel Muthaiah, V.M.; Meka, S.R.; Manoj Kumar, B.V.
ABSTRACT: The present study explores the reactivity of nanosized silicon carbide (SiC) with nitrogen gas in forming silicon nitride (Si3 N4 ). As-received micron-sized SiC particles were reduced to nanosized SiC particles by high-energy ball milling. Further, the ball-milled powders were heat-treated at 1300°C, 1400°C and 1500°C for 2 h in argon and nitrogen atmospheres. The heat-treated powders were characterised by employing X-ray diffraction, scanning electron microscopy, transmission electron microscopy, differential thermal analysis and thermogravimetric analysis. Heat-treatment in nitrogen atmosphere resulted in the development of amorphous and crystalline Si3 N4 nanowires/fibers/threads from the surface of nanosized SiC particles. The morphology of developed nanostructures showed a dependence on the heat-treatment temperature. The nanosized SiC powders with nanowires/fibers/threads of Si3 N4 grown on their surfaces could be used as an effective reinforcement to produce novel composites.